Integrated Characterization of Cuban Germplasm of Cocoyam (Xanthosoma Sagittifolium (L.) Schott) - D. Milián Jiménez Marilys; Molina Concepción Osmany; Figueroa Aguila Yadelys (Journal of Plant Genetics and Crop Research, 2018)
The present study aims at integrating the characterization studies conducted on the Cuban germplasm collection of Xanthosoma sagittifolium (Araceae) preserved in the Research Institute of Tropical Roots and Tubers Crops (INIVIT). Differentiation of accessions was done by combining qualitative and quantitative descriptors to clarify the relationships between six well-defined groups. The results may be used to establish a core collection for improved management of Xanthosoma spp. germplasm.
Keywords: Aroids